Rehabilitation Planning for Flexible Pavement using Rebound Deflection Method and PCI Method on Triwidadi Road of Yogyakarta - Adly, Emil; Widodo, Wahyu; Rahmawati, Anita; Sri Atmaja Putra, J. N. N. R. (International Journal of Integrated Engineering, 2019)
Triwidadi Road, located in the Pajangan area, Bantul, Special Region of Yogyakarta Province in Indonesia is characterised as local road in accordance to its function, and is classified as poor category based upon the PCI results. Damages scattered on the road section often cause an uncomfortable feeling of the road users, and may also potentially cause traffic accidents. An overlay addition is considered to be a solutive alternative to improve the road pavement structure in order to ensure its appropriateness and service quality to the road users. This study uses the rebound deflection method with the Benkelman Beam which is based on the Pd T-05-2005-B regulation. The studied road was 4 km long, stationing at 14+000 - 18+000 with 50 meters range between one tested point to another, and was made as many as 20 segments. The results show that there is no significant correlation between functional layer damages with the structural road, which is shown from the comparison between data analysis with PCI result which stating the corrected overlay, hence recommendation solutions that can be offered to be performed are as follows: overlay addition for all segments are 4 cm, with Laston asphalt type with Resilient Modulus = 2000 MPa and Marshall Stability = 800 kg for a 10-year design life with CESA = 1,480,000 ESA.